Whores of Babylon : Catholicism, gender, and seventeenth-century print culture - Dolan, Frances E. (Frances Elizabeth), 1960- (Ithaca, N.Y. : Cornell University Press, 1999)
"In the seventeenth century, the largely Protestant nation of England was preoccupied with its Catholic subjects. They inspired more prolific and harsher criticism and more elaborate attempts at legal regulation than did any other minority group. To understand this phenomenon, Frances E.
Dolan probes the verbal and visual representations of Catholics and Catholicism and the uses to which these were put during three crises in Protestant-Catholic relations: the gunpowder plot (1605), Queen Henrietta Maria's open advocacy of Catholicism in the 1630s and 1640s, and the popish and meal tub plots (1678-1680). She uses each crisis as a jumping-off point, an opportunity for speculation, as did contemporary writers.
Drawing on political and legal writings and offering fresh readings of literary texts such as Macbeth and Antony and Cleopatra, Dolan shows how often Catholics and Catholicism were linked to disorderly women."--BOOK JACKET.
1. "Home-Bred Enemies": Imagining Catholics -- 2. Searching the Bed: Jacobean Anti-Catholicism and the Scandal of Heterosociality -- 3. The Command of Mary: Marian Devotion, Henrietta Maria's Intercessions, and Catholic Motherhood -- 4. "The Wretched Subject the Whole Town Talks of": Elizabeth Cellier, Popish Plots, and Print.
Includes bibliographical references and index.
Keywords: Catholic Church -- Controversial literature -- History and criticism; Catholics -- England -- History -- 17th century; Catholic women -- England -- History -- 17th century; English literature -- Early modern, 1500-1700 -- History and criticism; Catholics -- England -- Public opinion -- History -- 17th century; Public opinion -- England -- History -- 17th century; England -- Church history -- 17th century